The Impact of Ghrelin in Metabolic Diseases: An Immune Perspective - Jéssica Aparecida da Silva Pereira; Felipe Corrêa da Silva; Pedro Manoel Mendes de Moraes-Vieira (Journal of Diabetes Research)
Obesity and insulin resistance have reached epidemic proportions. Obesogenic conditions are associated with increased risk for the development of other comorbidities and obesity-related diseases. In metabolic disorders, there is chronic low-grade inflammation induced by the activation of immune cells, especially in metabolic relevant organs such as white adipose tissue (WAT). These immune cells are regulated by environmental and systemic cues. Ghrelin is a peptide secreted mainly by X/A-like gastric cells and acts through the growth hormone secretagogue receptor (GHS-R). This receptor is broadly expressed in the central nervous system (CNS) and in several cell types, including immune cells. Studies show that ghrelin induces an orexigenic state, and there is increasing evidence implicating an immunoregulatory role for ghrelin. Ghrelin mainly acts on the innate and adaptive immune systems to suppress inflammation and induce an anti-inflammatory profile. In this review, we discuss the immunoregulatory roles of ghrelin, the mechanisms by which ghrelin acts and potential pharmacological applications for ghrelin in the treatment of obesity-associated inflammatory diseases, such as type 2 diabetes (T2D).